Caracterização de um iflavírus multiespecífico isolado de pentatomídeos-praga da agricultura - Santos, Ethiane Rozo dos (2022)
Iflaviruses are arthropod viruses that may or may not cause symptoms in their hosts. Usually, whose studies are restricted to sequencing, genome description, and evolutionary analyses. This was the case of the iflavirus Halyomorpha halys virus (HhV), originally described from the transcriptome of healthy Halyomorpha halys. H. halys is an Asian stink bug, invasive in North America with great importance for agriculture, but not present in Brazil. In Brazil, the ecological niche is efficiently occupied by endemic species such as Euschistus heros, Chinavia ubica and Dichelops melacanthus. In an attempt to understand more deeply the relationship between asymptomatic iflavirus and host, this thesis aimed to characterize the HhV virus at different levels in relation to H. halys and to the three species of bugs endemic to Brazil. Through the antenna transcriptome of the three species arising from laboratory colonies, genomes of three HhV isolates with high copy number were found here. The viruses found were evaluated for genome characteristics, phylogenetic relationships, replication level, prevalence, sequence similarity and appearance of the isolated particle. All the results confirmed that they were HhV isolates, which, in addition to being multi-specific, have a wide geographic distribution and replicates at very high levels in insects. It is still unclear how the same virus infects geographically distant insects; although apparently present in low proportion in the field. Thus, in an attempt to elucidate such transmission mechanisms, we investigated whether the pentatomid egg-parasitoid wasp Telenomus podisi, widely distributed throughout America and which parasitizes all four species, could be a vehicle for HhV. The total body transcriptome of T. podisi was carried out and the complete genome of HhV was found. However, HhV was in much lower copy number than in the context of pentatomid infection. Two of four pools of 50 microwasps were positive for HhV. In this thesis, many fundamental questions were generated, such as the route of infection and transmission, prevalence in the field or how the infection can influence the insect's sensitivity to chemical insecticide. However, the results found here indicate a sophisticated persistent interaction between iflavirus and host, and open possibilities of understanding for uses of asymptomatic iflavirus as bioinsecticides associated with other lethal tools or as biotechnological tools.